MENINGKATKAN PERAN BADAN USAHA MILIK DESA DALAM MEMASARKAN PRODUK UNGGULAN LOKAL - Julianto Hutasuhut; Abd. Rasyid Syamsuri; Adrial Falahi; Ardhansyah Putra Harahap; Arief Hadian; Dwi Saraswati; Siti Lam'ah Nasution (LPPM Universitas Bina Bangsa, 2023)
Village-Owned Enterprises (BUMDes) have emerged as a novel alternative approach to enhancing the economy and welfare of rural communities by tapping into the potential of villages. However, the reality is that only a few BUMDes are able to positively contribute to economic development and the betterment of community welfare, including those in Pematang Johar village. To address this, a community service initiative was conducted in Pematang Johar village in the Medan Labuhan District of Deli Serdang Regency. The main objective of the program was to provide education and socialization on the